Sinus floor elevation or referral for further diagnosis and therapy: A comparison of maxillary sinus assessment by ENT specialists and dentists using cone beam computed tomography. Issue 5 (12th February 2020) - Janner, Simone F. M.; Dubach, Patrick; Suter, Valerie G. A.; Caversaccio, Marco D.; Buser, Daniel; Bornstein, Michael M.
Abstract: Objectives: To compare ear, nose, and throat (ENT) specialists and dentists assessing health or pathology of maxillary sinuses using cone beam computed tomography (CBCT). Material and methods: Two ENT specialists and two oral surgeons assessed 100 CBCT datasets of healthy patients referred for dental implant placement in the posterior maxilla and decided on the possibility of sinus floor elevation or the necessity for further diagnostic examinations based solely on radiographic findings. Inter‐rater agreements within the same specialty were calculated with Cohen's kappa and overall agreements with Fleiss kappa, and factors influencing the decisions taken were evaluated using regression analyses. Results: The correlation between all four raters was generally fair to moderate. The intra‐specialty comparison showed a lower correlation between dentists than between ENT specialists. Absence of membrane thickening and total or subtotal sinus opacification showed the highest predictive value for a consensus in favor of sinus floor elevation and ENT referral, respectively. Flat membrane thickening with an irregular surface morphology was associated with disagreement between the examiners. Dome‐shaped membrane thickenings were often considered as to be referred by dentists but not by ENTs. Conclusion: The assessment of maxillary sinuses using CBCT imaging exhibited unsatisfactory agreement between ENT specialists and oral surgeons. Referral guidelines based on accidental CBCT findings that aim to diagnose relevant sinus pathologies early and avoid unnecessary diagnostics and/or therapies are needed, and an initial proposal for such recommendations is provided. Further research on correct interpretation of sinus findings and a validation of the present recommendations are required.